Establishment of a thermal process for dried-salted herring (Sardinella fimbriata) in oil - Ventura, Sharon Rodriguez
ABSTRACT This study aims to establish the thermal process of tuyo in oil using dried-salted herring as main raw material. Phase I dealt with the selection of the most acceptable formulation. of tuyo in oil with different types of vegetables oils, salt content of tuyo and various seasonings as variant using Consumer Acceptability and Descriptive Tests. The base formulation was developed from the published formulation of Tressler et al (1974) for canned sardines in oil modified base on the ingredients recorded in commercially available bottled tuyo in oil in local retail markets. The most acceptable vegetable oil for the formulation of tuyo in oil was corn oil. However, improvements were needed to decrease the saltiness of tuyo used in the initial formulation. It was established that the most acceptable salt content of tuyo for the product was 7.15%. The sensory evaluation also indicated that the tuyo in corn oil with chili labuyo instead of chili powder as seasoning was most acceptable. Heat penetration study and process calculation of the selected formulation of tuyo in oil packed in 237ml glass jars showed that the mean thermal process time (B) and the mean operator's processing time (Pt) at 250°F were 7.87 and 13.48 min, respectively. Verification of the process showed that the lethality (Fc) of the process was 11.845 min, which indicated adequacy of the process. Sensory evaluation of the finished product by a 40 member panel showed that the panelists gave the color, mouthfeel, texture, flavor, spiciness, saltiness, sourness, and overall acceptability of the thermal processed tuyo in oil ratings of like moderately. The thermally processed tuyo in oil sample was described as slightly brown in color, slightly moist in terms of mouthfeel, firm but tender, slightly spicy, slightly salty, and has adequate sour and moderately recognizable flavor. Physico-chemical analysis showed that the tuyo in oil has a pH of 5.2 and Aw of 0.94. the product also contained a vacuum of 23.50 in Hg, headspace of 0.60 in, gross weight of 361.30± 10g and net weight of 213.85± 10g. Microbiological examination showed negative results for mesophilic anaerobic sporeformers, thermophilic sporecount and thermophilic anaerobic sporeformers. However, the test for aerobic mesophiles showed a growth of 10 to 2 cfu/g for one bottle tested. This was attributed to possible post-process contamination. Contaminating microorganisms in the cooling water may have gained access into the bottled tuyo in oil during coolin